CEA-, Her2/neu-, BCRP- and Hsp27-positive microparticles in breast cancer patients - Liebhardt, Susanne; Ditsch, Nina; Nieuwland, Rienk; Rank, Andreas; Jeschke, Udo; Koch auf Rohrbach, Franz von; Friese, Klaus; Toth, Bettina (Anticancer research, 2010)
Background: This is the first prospective case-control study that evaluates the expression of tumour-specific antigens on circulating microparticles (MP) in breast cancer patients and in women with benign breast tumour. Materials and Methods: MP were determined by flow cytometry in patients with breast cancer (n=34; T1 (n=19) and T2 (n=15)) and women with benign breast tumour (n=19). Results: Patients with lymph node metastases (N1, n=9) showed significantly higher numbers of annexin V+ MP (p=0.042), CD66+ MP (p=0.045), BCRP1+ MP (breast cancer resistance protein) (p=0.025) and Hsp27+ MP (p=0.034) than controls. Furthermore, T1 patients had significantly higher levels of annexin V+ MP (p=0.004), CD66+ MP (p=0.025), BCRP1+ MP (p=0.008) and Hsp27+ MP (p=0.02) than controls. Conclusion: Significant differences are present between breast cancer patients with lymph node metastases and controls concerning annexin V-, CD66-, BCRP1- and Hsp27-positive MP. To specify the role of these MP subpopulations in breast cancer progression, further studies enrolling larger patient groups are part of ongoing research.